Agriculture in Ancient Sanskrit Texts: Relevance in Modern Nepal - Adhikari, Sudhir Kumar (Economic Journal of Nepal, 2012)
There are large numbers of ancient Sanskrit texts that include agricultural science in them. Manuscripts like Vedas, Krishi-Parashara, Kautilya’s Arthashastra consist of valuable information about agronomy. Selections of seeds, land preparation, water management and irrigation, pest control, storage, crop rotation and so on are the topics described in them. There is a treasure of knowledge on agriculture in ancient Sanskrit text. Nepal, as an agricultural country, is lagging behind to fulfill the basic needs of general people along with economic depletion. Agro-economics can be benefited from the principles described in above mentioned ancient Sanskrit texts. Therefore, this paper seeks to preview a brief arm-chaired survey of our ancient literatures. The effort especially focuses on Vedas, Krishi-Parashara and Kautilya’s Arthashastra with special reference to agriculture focusing relevance in contemporary Nepal. The Economic Journal of Nepal, Vol. 35, No. 1, January-March 2012 (Issue N0. 137)